Examination of E-Sports Participation and Motivation Levels of Students in Sports Sciences Faculty - Söyler, Didem Yavuz; Bulut, Mesut (Hasan ŞAHAN, 2025)
ÇThe aim of the study is to examine the e-sports participation and motivation levels of students studying at the Faculty of Sports Sciences at Fırat University in terms of some demographic variables. The universe of the study was the Faculty of Sports Sciences at Fırat University, while the sample consisted of 338 students studying at four departments of this faculty. A questionnaire was used as the data collection tool in the study and this questionnaire consists of two main parts. The first part includes questions aimed at obtaining the socio-demographic information of the participants. In the second part of the questionnaire, “E-Sports Participation Motivation Scale” was used, this scale consists of 47 items and five different sub-dimensions. SPSS 25 software was used in the analysis of the data. The reliability of the scale was evaluated with Cronbach Alpha test and ?=0.897 value was obtained. In addition, frequency and percentage distributions related to categorical variables are presented. Since it was observed that the data showed a normal distribution, independent t test was used for group comparisons and One-Way Analysis of Variance (ANOVA) was used for three or more group comparisons. The statistical significance level in the study was determined as 0.05. As a result of the research, it was seen that the participation and motivation levels of male students in e-sports were higher than female students, those who said yes according to the status of doing sports were higher in the taxonomic field sub-dimension, and when the anova test was examined according to the class variable of the participants, the difference was between the 1st and 2nd grades in the taxonomic field sub-dimension and between the 3rd and 4th grades in the relational self sub-dimension.

Çalışmanın amacı Fırat Üniversitesi spor bilimleri fakültesinde okuyan öğrencilerin bazı demografik değişkenler açısından e-spora katılım ve motivasyon düzeylerinin incelenmesidir. Fırat Üniversitesi spor bilimleri fakültesinde okuyan 1453 öğrenci oluştururken örneklemi ise bu fakültedeki dört bölümde okuyan 338 öğrenci oluşturmuştur. Çalışmada veri toplama aracı olarak bir anket kullanılmıştır ve bu anket iki ana bölümden oluşmaktadır. İlk bölümde katılımcıların sosyo-demografik bilgilerini edinmeye yönelik sorular yer almaktadır. Anketin ikinci kısmında, “E-Spor Katılım Motivasyonu Ölçeği” kullanılmış olup, bu ölçek 47 maddeden oluşmakta ve beş farklı alt boyuttan oluşmaktadır. Verilerin analizinde SPSS 25 yazılımı kullanılmıştır. Ölçeğin güvenilirliği, Cronbach Alpha testi ile değerlendirilmiş ve ?=0,897 değeri elde edilmiştir. Ayrıca, kategorik değişkenlerle ilgili frekans ve yüzde dağılımları sunulmuştur. Verilerin normal dağılım gösterdiği gözlemlenmiş olduğundan, grup karşılaştırmaları için bağımsız t testi, üç ve daha fazla grup karşılaştırmaları için ise Tek Yönlü Varyans Analizi (ANOVA) kullanılmıştır. Araştırma sonucunda çalışmaya katılan öğrencilerin erkek öğrencilerin kadınlara oranla e-spora katılım ve motivasyon düzeylerinin yüksek olduğu, spora yapma durumuna göre evet diyenlerin taksonomik alan alt boyutunda daha yüksek olduğu, katılanların sınıf değişkenine göre anova testine bakıldığında farklığın taksonomik alan alt boyutunda 1. sınıf ve 2. sınıf arasında ilişkisel benlik alt boyutunda 3.sınıf ve 4.sınıflar arasında olduğu görülmüştür.
Spor Bilimleri Fakültesindeki Öğrencilerin E-Spora Katılım ve Motivasyon Düzeylerinin İncelenmesi
Keywords: Sports and Recreation; Spor ve Rekreasyon